Analysis of the life course effects of the disability dilemma among rural older adults in China - Fen Li; Xiangdong Gao; Yahui Meng (Frontiers Media S.A., 2024)
ObjectiveTo analyse whether the accumulation of early adverse experiences among individuals of different generations has an impact on disabilities and evaluate the cumulative effects of disadvantages in rural older adults in China.MethodsA Binary Logit Model was used to analyse the life course effects of the disability dilemma among rural older adults.ResultsRegarding Activities of Daily Life (ADLs), there was no significant difference between older adults that experienced 1 adverse events and the control group. The probability of older adults experiencing difficulties in 2, 3, 4, or more types of ADLs was 1.486 times, 2.173 times, and 3.048 times higher than that of the control group, respectively. Regarding Instrumental Activities of Daily Life (IADLs), there was no significant difference between the population that experienced 1 or 2 adverse events and the control group. The probability of experiencing difficulties in 3, 4, or more types of IADLs was 1.527 times and 1.937 times higher than that of the control group, respectively. Early adverse events had a cumulative disadvantageous effect on disability in older adults. The longer the duration of adverse experiences, the higher the risk of disability in old age. Education had a significant mitigating effect on health risks.ConclusionPay attention to early factors in the life course, strengthen the promotion of health prevention concepts, and pay attention to the moderating and relieving effects of education on health. We should also gradually improve the rural disability care system and family health security capabilities in China's rural areas.